2015
DOI: 10.1007/s00894-015-2631-3
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolo[3,4-d]pyrimidines as novel inhibitors of O-acetyl-l-serine sulfhydrylase of Entamoeba histolytica: an in silico study

Abstract: Amoebiasis, a worldwide explosive epidemic, caused by the gastrointestinal anaerobic protozoan parasite Entamoeba histolytica, infects the large intestine and, in advance stages, liver, kidney, brain and lung. Metronidazole (MNZ)-the first line medicament against amoebiasis-is potentially carcinogenic to humans and shows significant side-effects. Pyrazolo[3,4-d]pyrimidine compounds have been reported to demonstrate antiamoebic activity. In silico molecular docking simulations on nine pyrazolo[3,4-d]pyrimidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In order to refine the modeled UCP1 protein, molecular dynamics (MD) simulation was performed on Desmond v3.8 modules from the Schrödinger suite software . The protein structure was prepared using the Protein Preparation Wizard module in the Schrödinger software . The NPT temperature is fixed to 300 K, the pressure is set to 1.01 bar, and the operation is 50 ns.…”
Section: Methodsmentioning
confidence: 99%
“…In order to refine the modeled UCP1 protein, molecular dynamics (MD) simulation was performed on Desmond v3.8 modules from the Schrödinger suite software . The protein structure was prepared using the Protein Preparation Wizard module in the Schrödinger software . The NPT temperature is fixed to 300 K, the pressure is set to 1.01 bar, and the operation is 50 ns.…”
Section: Methodsmentioning
confidence: 99%
“…Shaw Research, New York, NY, 2015), running CentOS7.1 Linux operating system. The operation was mainly conducted on well-prepared structures in several phases [38]. Initially, a model system for generating a solvated system was built with the solvent model set to predefined SPC [33], box shape to orthorhombic and box size calculation to Buffer method through the System Builder panel [39, 40].…”
Section: Methodsmentioning
confidence: 99%
“…These structural determinants extracted from crystal structures of various peptide-enzyme complexes formed the basis for developing peptide/nonpeptide inhibitors. Since then several studies have reported inhibitors against open conformation of CysK from different organisms with affinities for CysK generally ranging from millimolar to micromolar concentrations (Jean Kumar et al 2013;Spyrakis et al 2013;Yadava et al 2015;Kant et al 2018). Natural compounds as potential inhibitors of CysK have also been reported, however, the leads from these studies require rational modifications to achieve better efficacy (Nagpal et al 2012;Mori et al 2015Mori et al , 2018.…”
Section: Inhibition By the Endogenous Cyse Peptidementioning
confidence: 99%